Kemampuan Berpikir Kritis Siswa SMP pada Pembelajaran IPA - Rori Khoirudin; Ashad; Moh. Masykuri (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
This research is a qualitative descriptive research with the aim to describe students' ability in construct critical thinking. The subjects of the study were the students of SMP Negeri 8 Surakarta city for the academic year 2019/2020 which amounted to 762 students, with a sample size of 200 students . Population choose random sample of each class. Instrument used consisted of test the critical thinking skills of students through a questionnaire with 20 statements questionnaire number . The questionnaire sheet was developed based on 6 indicators that were the focus of the study. The indicator in question is a discussion that is able to ask questions, answer questions, solve problems, make conclusions, question and assess the results of observations . The results showed that if seen from the average level of student achievement on each indicator, the average achievement on the indicator analyzing argument is 72,28%, on the indicator of asking ability is 78,55%, on the indicator answering questions is 78,35%, on the indicator of solving the problem is 61,95%, the indicator makes a conclusion is 55,45%, and the indicator of the skill of evaluating and evaluating the results of observations is 72.50%. The results also showed that in general students of SMP Negeri 8 Surakarta had critical thinking skills with quite critical criteria, with 8 students classified as very non critical (4%), who were classified as non-critical were 47 students (23,5%), who were classified as as quite critical were 133 students (66,5%), who were classified as critical were 10 students (5%), and those classified as very critical were 2 students (1%). This proves that students' critical thinking skills still need to be trained further in order to be improved.